2016
DOI: 10.17140/tfmoj-1-106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Cypermethrin on the Onset of Puberty and Ovarian Biomarkers in Female Prepubertal Rat: Attenuating Role of Zinc

Abstract: Cypermethrin, a synthetic pyrethyroid pesticide, is used for more than one decade to control a wide variety of pests in agriculture. The present study designed to evaluate the protective role of zinc in attenuating cypermethrin induced reproductive toxicity in female prepubertal rat. Female prepubertal rat received oral cypermethrin alone at two dose levels and zinc alone or combined with cypermethrin for consecutive 14 days. Cypermethrin arrested vaginal opening, reduced the weights of ovaries and uterus. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Such decrease indicate that cypermethrin may obstruct ovarian function. 3 Another study have shown that cypermethrin exposure can affect ovarian damage to tissue structure as well as in the ovarian function.…”
Section: Introductionmentioning
confidence: 99%
“…Such decrease indicate that cypermethrin may obstruct ovarian function. 3 Another study have shown that cypermethrin exposure can affect ovarian damage to tissue structure as well as in the ovarian function.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini sesuai dengan penelitian sebelumnya bahwa paparan Sipermetrin mengakibatkan terjadinya penurunan yang signifikan terhadap kadar FSH, LH dan estrogen (Das et al, 2016). Sejalan dengan penelitian lain oleh Solati et al (2010) (Auvichayapat et al, 2008).…”
Section: Pembahasan Ekstrak Etanol Teh Hijau Meningkatkan Kadar Fsh Punclassified